Investigating the Influence of Trashed Polymeric Compounds (TPC) on the Mechanical Properties, XRD Pattern and Microstructure of the Brick - Naheed Akhtar; Umer Zada; Ayaz Ahmed Soomro; Muhammad Arif; Muhammad Saad; Rahman Ullah (Journal of ICT, Design, Engineering and Technological Science, 2024)
Burnt clay brick is one of the major and widely used building units in masonry construction around the globe. The manufacturing of burnt clay bricks using waste plastics can minimize the environmental overburden caused by waste plastic deposition on open landfills and would also improve the brick performance at low production cost leading to more sustainable construction. This study aims to evaluate the effect of the waste Plastic in the clay bricks. In this study, the waste plastics were collected from local garbage areas respectively. Brick specimens were manufactured at an industrial brick kiln plant using various dosages (4%, 8%, and 12% by weight). The mechanical and durability properties along with microstructure of these bricks were studied. It was observed that clay bricks incorporating waste plastics have lower compressive strength compared to clay bricks without waste plastic. Scanning Electron Microscopy (SEM) analysis confirms the porous microstructure of the brick specimens incorporating plastics, which resulted in lesser unit weight leading to lighter and more economical structures. Furthermore, resistance against efflorescence was improved in all the tested bricks incorporating plastics. Based on this study, the thermal conductivity will be decreased if the shredded plastic in the bricks is increased. The weight of the brick also decreases if the shredded plastic in the brick is increased. The water absorption ratio will also be decreased if the plastic content in the bricks are increased. Overall implication of the study is it mitigates the plastic pollutions in the society and could reduce the issues of the carbon emissions to contribute to the struggle to fight climate change. The study indicates many economic benefits such as cost saving and could create different business ideas involving the recyclable plastic based bricks production ultimately boosting the economy.